2000
DOI: 10.1126/science.289.5485.1769
|View full text |Cite
|
Sign up to set email alerts
|

Myotonic Dystrophy in Transgenic Mice Expressing an Expanded CUG Repeat

Abstract: Myotonic dystrophy (DM), the most common form of muscular dystrophy in adult humans, results from expansion of a CTG repeat in the 3' untranslated region of the DMPK gene. The mutant DMPK messenger RNA (mRNA) contains an expanded CUG repeat and is retained in the nucleus. We have expressed an untranslated CUG repeat in an unrelated mRNA in transgenic mice. Mice that expressed expanded CUG repeats developed myotonia and myopathy, whereas mice expressing a nonexpanded repeat did not. Thus, transcripts with expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
703
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 662 publications
(730 citation statements)
references
References 27 publications
24
703
2
1
Order By: Relevance
“…Standard mouse anesthetics were cardiotoxic, especially in mice with preexisting conduction defects, and after extensive experimentation we settled on the valium and ketamine combination. We performed and scored EMGs as previously reported 7 . We performed three lead ECGs using a BioAmp/Powerlab from ADInstruments and collected data on a computer for later analysis.…”
Section: Emgs and Ecgsmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard mouse anesthetics were cardiotoxic, especially in mice with preexisting conduction defects, and after extensive experimentation we settled on the valium and ketamine combination. We performed and scored EMGs as previously reported 7 . We performed three lead ECGs using a BioAmp/Powerlab from ADInstruments and collected data on a computer for later analysis.…”
Section: Emgs and Ecgsmentioning
confidence: 99%
“…2 ). Myoblast cell culture models 5,6 and subsequently a transgenic mouse model 7 have provided strong evidence for the involvement of RNA containing expanded CUG repeat tracts in aspects of DM1 skeletal muscle pathology. However, there is no clear model of RNA toxicity in the heart, and instead it has been suggested that DM1 cardiac pathology may be due to misexpression of DMPK 8,9 .…”
mentioning
confidence: 99%
“…In this transgenic mouse model, the expanded repeat is inserted in a genomic fragment containing the entire human skeletal actin gene, including the 5' regulatory sequences, and the pattern of transgene expression is similar to endogenous skeletal actin [20,29]. To our knowledge, the paucity of ribonuclear foci at the NMJ in HSA LR transgenic mice is the first evidence that genes encoding myofibrillar proteins are downregulated in subsynaptic nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord tissue was obtained at autopsy and stored at -70°C. HSA LR transgenic mice that express CUG exp RNA in skeletal muscle were described previously [20]. CUG exp expression in these transgenic mice is controlled by regulatory elements from the human skeletal actin gene, which results in ribonuclear foci, myotonia, myopathy, and a spliceopathy that is similar to human DM1 [6].…”
Section: Tissue Samplesmentioning
confidence: 99%
“…1,2 Although it has been suggested that haploinsufficiency and position effect variegation may contribute to DM1 phenotype, there is increasing evidence that the accumulation of mutant DMPK mRNA with expanded CUG repeats [3][4][5][6][7][8] has a central function in the pathogenetic mechanism. 9,10 Induced expression of expanded CUG repeats in a transgenic mouse model resulted in a DM1 phenotype, which reverted to normal when the induction was switched off. 11 This provided strong evidence that blockade of mutant DMPK transcript accumulation can restore cellular functions.…”
Section: Introductionmentioning
confidence: 99%